Fisher’s Adaptation Strategiesinsmall islandsto the Impactsof Climate Change (A case study in Pulau Panjang Village, Subi District, Natuna Regency, Riau Island) - Wibowo, Ari; Satria, Arif (Sodality: Jurnal Sosiologi Pedesaan, 2015)
This study aime to analyzethe effect ofclimate change onsocio-economic conditionsof fisher, as well as to identifyadaptation and mitigation strategies related to climate change. The method inthis study usingquantitative and qualitative methods. The results showed thattheeffectof climate changeonsocio-economic aspects offishing. Influenceonsocio-economic aspects ofthesearenotnecessarilythe calendarseason, the loss ofsome of the animalsthat becamea markerdeterminationseason, andincreased intensity of stormsat seawhichinterfere withthe activityof fisher catching. Therefore, the right strategy is needed to transform fisher’s adaptation on adjusting with climate change. The types of adaptational strategy are divided into: the diversification of economic activities; the investment on fishing technology; maintaining good relationship with other fishers; finding new catchment areas; and utilizing social relationship and mobilizing members of the family.Keywords: adaptationstrategy, climate change,fisher, small islands